Rediscovery and description of the quagga shark, Halaelurus quagga (Alcock, 1899) (Chondrichthyes: Scyliorhinidae) from the southwest coast of India - Akhilesh, K. V.; Bineesh, K. K.; Shanis, C. P.r.; Human, B. A.; Ganga, U. (Zootaxa, 2011)
The Quagga shark Halaelurus quagga (Alcock, 1899) is one of the poorest known scyliorhinid (Carcharhiniformes) sharks of the world, described from a single specimen collected from the Arabian Sea coast of India (off Malabar). Since its description, the only other published reports of this species are of specimens from Somalia. This paper reports on H. quagga from Indian waters, more than 100 years after its description, and only the third report of specimens of this species globally. A re-description of H. quagga is also provided based on the recent Indian specimens.